Comparative risk assessment of vehicle maintenance activities: Hybrid, battery electric, and hydrogen fuel cell cars - López-Arquillos, Antonio; Rubio-Romero, Juan Carlos; Suárez-Cebador, Manuel; Pardo-Ferreira, María del Carmen (My University, 2015)
In this research, vehicle maintenance activities and their safety risks were statistically analyzed. This study focused on three types of vehicle: hybrid, battery electric, and hydrogen fuel cell cars. The repair activities and the risks for each power train technology were identiﬁed by a panel of experts. Depending on its frequency and severity, risk values were calculated for each maintenance activity. The method chosen was the staticized group method, which involves collection opinions from a panel of experts. The ten experts ﬁnally chosen were asked to anonymously respond to a survey that had been especially designed to reduce bias and ensure the quality of the data. The most dangerous vehicle maintenance activities were the manipulation of asbestos, charging and discharging of high value capacitors, and welding.
Keywords: Vehículos eléctricos; Safety risk; Maintenance; Battery electric vehicle; Hybrid vehicle; Hydrogen fuel cell vehicle